Enhancement and Civic Virtue - Jefferson, Will (2014)
Opponents of biomedical enhancement frequently adopt what Allen Buchanan has called the Personal Goods Assumption. On this assumption, the benefits of biomedical enhancement will accrue primarily to those individuals who undergo enhancements, not to wider society. Buchanan has argued that biomedical enhancements might in fact have substantial social benefits by increasing productivity. We outline another way in which enhancements might benefit wider society: by augmenting civic virtue and thus improving the functioning of our political communities. We thus directly confront critics of biomedical enhancement who argue that it will lead to a loss of social cohesion and a breakdown in political life.